Chemical Constituents and Biological Activities of Ficus tikoua Bureau - Liangliang Yao; Shengchao Zhao; Wei Liu; Guanzhen Wang; Chunpeng (Craig) Wan (Journal of Chemistry)
Ficus tikoua Bureau (F. tikoua Bur.) is a perennial woody vine in the Moraceae family that has been used as a traditional folk medicine for centuries to treat many diseases such as chronic bronchitis, diarrhea, dysentery, rheumatism, and other inflammation-related diseases in certain parts of China, India, Vietnam, and Laos. This medicinal plant contains beneficial secondary metabolites belonging to various chemical classes, including flavonoids, phenolics, terpenoids, steroids, coumarins, and alkaloids. In this review, we have summarized the natural compounds isolated from F. tikoua Bur. and their biological effects.